Parathyroid hormone-related protein promotes bone loss in T-cell leukemia as well as in solid tumors. Issue 2 (28th January 2020) - Kohart, Nicole A.; Elshafae, Said M.; Demirer, Aylin A.; Dirksen, Wessel P.; Breitbach, Justin T.; Shu, Sherry T.; Xiang, Jingyu; Weilbaecher, Katherine N.; Rosol, Thomas J.
Abstract: Parathyroid hormone-related protein (PTHrP) and macrophage inflammatory protein-1α (MIP-1α) are important factors that increase bone resorption and hypercalcemia in adult T-cell leukemia (ATL). We investigated the role of PTHrP and MIP-1α in the development of local osteolytic lesions in T-cell leukemia through overexpression in Jurkat T-cells. Injections of Jurkat-PTHrP and Jurkat-MIP-1α into the tibia and the left ventricle of NSG mice were performed to evaluate tumor growth and metastasis in vivo . Jurkat-pcDNA tibial neoplasms grew at a significantly greater rate and total tibial tumor burden was significantly greater than Jurkat-PTHrP neoplasms. Despite the lower tibial tumor burden, Jurkat-PTHrP bone neoplasms had significantly greater osteolysis than Jurkat-pcDNA and Jurkat-MIP-1α neoplasms. Jurkat-PTHrP and Jurkat-pcDNA cells preferentially metastasized to bone following intracardiac injection, though the overall metastatic burden was lower in Jurkat-PTHrP mice. These findings demonstrate that PTHrP induced pathologic osteolysis in T-cell leukemia but did not increase the incidence of skeletal metastasis.